2016
DOI: 10.12693/aphyspola.129.241
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Ultraviolet Surface Modification of Polyethylene Terephthalate (PET) for Surface Structuring and Wettability Control

Abstract: The surface modification of polyethylene terephthalate (PET) polymer films has been performed by irradiation of extreme ultraviolet photons to investigate the effect of surface structuring on wettability control. For biomedical engineering applications, surface structuring and wettability control of PET films could enhance the polymer biocompatibility by promoting cell adhesion and consequently proliferation. The PET films are irradiated with laser plasma extreme ultraviolet source based on double stream gas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…The surface roughness by itself could also affect the hydrophilicity of the surface. Ahad and collaborators [18] studied the surface modification of PET films by irradiation with extreme ultraviolet photons to further evaluate the effects on the surface structure and wettability. Results showed that the water contact angle increased with an increased surface roughness.…”
Section: Functionalisationmentioning
confidence: 99%
“…The surface roughness by itself could also affect the hydrophilicity of the surface. Ahad and collaborators [18] studied the surface modification of PET films by irradiation with extreme ultraviolet photons to further evaluate the effects on the surface structure and wettability. Results showed that the water contact angle increased with an increased surface roughness.…”
Section: Functionalisationmentioning
confidence: 99%
“…The detailed description of the source is given elsewhere [9][10][11]. The polymer sample holder was kept 2 mm away from the EUV collector focal point.…”
Section: Ptfe Foils 01 MM Thick Obtained From Goodfellowmentioning
confidence: 99%
“…The polymer samples were irradiated with 50 or 300 EUV shots at 10 Hz repetition rate in the presence of EUV-ionized nitrogen gas in the interaction region [12]. The detailed arrangement and working of the source on PTFE and other polymers for application in biomedical engineering are documented before [11,13]. Cells grown on samples for 24, 48, 72, and 96 h and prepared for fluorescent microscopy according to procedures described elsewhere [14].…”
Section: Ptfe Foils 01 MM Thick Obtained From Goodfellowmentioning
confidence: 99%
“…The contamination of the process is easily avoided, offers high processing speed, easy automation, and the possibility to treat large areas by controlling the parameters of the laser process [18]. Therefore, laser technology has been used for surface modifications of materials, especially polymers like ultra-High-Molecular-Weight Polyethylene (UHMWPE) [19][20][21], polypropylene (PP) [22,23], Polyethylene (PE) [24,25], Polycarbonate (PC) [26,27], polytetrafluoroethylene (PTFE) [28], Polyimide (PI) [29] and PEEK, in some studies [30].…”
Section: Introductionmentioning
confidence: 99%